The mechanism of the capillary oscillation and its application to fabrics’ sweat permeability - Liu, Yu; Chen, Hongxia; Chen, Lifen (Frontiers in Physics, 2023)
The capillary effect plays an important role in air and moisture permeability, and it can be used for thermal enhancement and energy harvesting. However, the capillary oscillation has not been extremely studied, and its mechanism for fabrics' sweat permeability was rare and preliminary. This paper studies the frequency property of the capillary oscillation in a zig-zag porosity of a fabric with a multiple layer structure. The theoretical analysis reveals that small porosity and low frequency of the zig-zag porosity are beneficial to the high sweat permeability. The proposed capillary oscillation probably paves a new avenue for designing fabrics with high moisture permeability, particularly in sportswear and military apparel in extreme cold environments.